Body Representation in Balinese Cultural Tourism: An Anthropological Study on Symbolism and Commodification - Anggara Putu Dharma Putra (International Journal of Social Studies, 2026)
This study addresses the growing importance of body representation within Balinese cultural tourism, where sacred Hindu aesthetics intersect with global tourism economies. While existing literature often emphasizes either symbolic meanings of the body in religious contexts or its commodification in tourism industries, a critical gap remains in understanding how these dimensions coexist and are negotiated in practice. This research aims to examine how the Balinese female body is constructed, represented, and commodified within cultural tourism spaces that simultaneously embody spirituality and commercial exchange. Employing a qualitative approach grounded in critical ethnography, the study was conducted over six months in Ubud, Seminyak, and Sanur (Denpasar). Data were collected through participant observation, 27 in-depth semi-structured interviews with key stakeholders, and document and media analysis. Field notes, interview transcripts, and visual-cultural materials were analyzed using thematic and symbolic interpretation supported by qualitative data software. The findings reveal that the female body in Balinese tourism operates as a hybrid cultural entity, functioning simultaneously as a sacred symbol in ritual contexts and as a commodified object within tourism and sexual economies. In ritual spaces, the body embodies spiritual values, purity, and cosmological harmony, while in tourism performances and spa industries, it is reframed as aesthetic and sensual capital. The study further identifies how sex workers actively negotiate identity and agency by appropriating cultural symbols, spiritual narratives, and traditional aesthetics to meet tourist expectations while maintaining personal boundaries. This duality produces a moral ambiguity within local communities, where the coexistence of sacred and profane practices is often tolerated through flexible cultural frameworks and economic considerations. The spatial and symbolic proximity between temples, spas, and nightlife venues further illustrates the blurred boundaries between spirituality and commodification. The study demonstrates that body representation in Balinese cultural tourism is not merely a process of sexualization but a complex reconfiguration of symbolic, economic, and cultural meanings. The body emerges as a contested site where religious values, global capitalism, and local agency intersect. This research contributes to anthropological discourse by proposing an integrated framework that bridges symbolic anthropology and tourism commodification, highlighting the need for culturally sensitive and ethically grounded approaches in managing tourism development in Bali.